The long and short of it from aphorism to novel - Morson, Gary Saul, 1948- (Stanford University Press, 2012)
This book explores the family of very short literary genres-- aphorisms, witticisms, wise sayings, and other short forms, from the perspective of their world views and the devices that express them.